Money Laundering and Its Grounds for Criminalization - Danish, Abdulmunir (Journal of Social Sciences - Kabul University, 2022)
In recent times, profiteers in various parts of the world have sought to accumulate wealth and capital by circumventing social and moral values, often resorting to illicit means to legitimize the proceeds of criminal activities. Traffickers, politicians, and criminals operating across different sectors of the economy have transferred economic power away from markets, governments, and citizens, instead channeling it into the hands of criminal individuals, groups, and organizations. This shift in economic power has had profoundly destructive effects on all components of society. However, with advancements and transformations in social, political, and economic domains, perpetrators of such crimes have increasingly sought ways to evade legal scrutiny. Despite these efforts, legal frameworks have been strengthened to hold them accountable for their activities.